Single-Assay Combination of Epstein-Barr Virus (EBV) EBNA1- and Viral Capsid Antigen-p18-Derived Synthetic Peptides for Measuring Anti-EBV Immunoglobulin G (IgG) and IgA Antibody Levels in Sera from Nasopharyngeal Carcinoma Patients: Options for Field Screening - Fachiroh, J. (American Society for Microbiology, 2006)
Assessment of immunoglobulin A (IgA) antibody responses to various Epstein-Barr virus (EBV) antigen complexes, usually involving multiple serological assays, is important for the early diagnosis of nasopharyngeal carcinoma (NPC). Through combination of two synthetic peptides representing immunodominant epitopes of EBNA1 and viral capsid antigen (VCA)-p18 we developed a one-step sandwich enzyme-linked immunosorbent assay (ELISA) for the specific detection of EBV reactive IgG and IgA antibodies in NPC patients (EBV IgG/IgA ELISA). Sera were obtained from healthy donors (n = 367), non-NPC head and neck cancer patients (n = 43), and biopsy-proven NPC patients (n = 296) of Indonesian and Chinese origin. Higher values of optical density at 450 nm for EBV IgG were observed in NPC patients compared to the healthy EBV carriers, but the large overlap limits its use for NPC diagnosis. Using either EBNA1 or VCA-p18 peptides alone IgA ELISA correctly identified 88.5% and 79.8% of Indonesian NPC patients, with specificities of 80.1% and 70.9%, whereas combined single-well coating with both peptides yielded sensitivity and specificity values of 90.1 and 85.4%, respectively. The positive and negative predictive values (PPV and NPV, respectively) for the combined EBNA1 plus VCA EBV IgA ELISA were 78.7% and 93.9%, respectively. In the Indonesia panel, the level of EBV IgA reactivity was not associated with NPC tumor size, lymph node involvement, and metastasis stage, sex, and age group. In the China panel the sensitivity/specificity values were 86.2/92.0% (EBNA1 IgA) and 84.1/90.3% (VCA-p18 IgA) for single-peptide assays and 95.1/90.6% for the combined VCA plus EBNA1 IgA ELISA, with a PPV and an NPV for the combined EBV IgA ELISA of 95.6 and 89.3%, respectively. Virtually all NPC patients had abnormal anti-EBV IgG diversity patterns as determined by immunoblot analysis. On the other hand, healthy EBV carriers with positive EBV IgA ELISA result showed normal IgG diversity patterns. By using EBV IgG immunoblot diversity as confirmation assay for EBV IgA ELISA-positive samples, the sensitivity and specificity for NPC diagnosis increased to 98% and 99.2%, respectively, in the Indonesian NPC samples. The use of these combined methods for seroepidemiological screening studies is proposed.